Synthesis of Al-Based Metal-Organic Framework in Water With Caffeic Acid Ligand and NaOH as Linker Sources With Highly Efficient Anticancer Treatment - Zeraati, Malihe; Rahdar, Abbas; Medina, Dora I.; Sargazi, Ghasem (Frontiers in Chemistry, 2021)
In this study, novel nanostructures of aluminum base metal-organic framework (Al-MOF) samples were synthesized using a sustainable, non-toxic, and cost-effective green synthesis route. Satureja hortensis extract was used as an effective source of linker for the development of the Al-MOF structures. Fourier-transformed infrared (FTIR) spectrum confirmed the presence of characterization bonds related to the Al-MOF nanostructures synthesized by the green synthesis route. The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analyses revealed that the sample synthesized by Na2-CA was composed of multilayers, although it was agglomerated, but it had dispersed and occurred in spherical particles, indicating active organic matter. N2 adsorption/desorption isotherms demonstrated the significant porosity of the Al-MOF samples that facilize the high potential of these nanostructure in medicine application. The anticancer treatment of Al-MOF samples was performed with different concentrations using the MTT standard method with untreated cancer cells for 24 h and 48 h periods. The results exhibited significant anticancer properties of Al- MOF samples developed in this study when compared with other MOF samples. Thus, the development of a novel Al-MOF and its application as a natural linker can influence the anticancer treatment of the samples.